2022
DOI: 10.3390/ani12233246
|View full text |Cite
|
Sign up to set email alerts
|

Body Condition and Breeding of Urban Red Squirrels: Comparison of Two Populations Affected by Different Levels of Urbanization

Abstract: The red squirrel is among the mammals that have adjusted well to urban habitats. Here, we focused on the two populations inhabiting Warsaw: in a park (with year-round supplemental feeding) and in an urban forest. We hypothesised that park squirrels would have higher body mass (and better body condition), being more stable over the year, and would have a higher breeding rate (i.e., the share of breeding females). Contrary to our hypothesis, forest squirrels were heavier and had better body condition than park s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 63 publications
1
16
0
Order By: Relevance
“…A contrasting pattern was reported for body mass and body condition of Eurasian red squirrels in two urban areas: a park located in the city centre of Warsaw and an area described as an urban forest (Beliniak et al. 2022). Squirrels were heavier with better body conditions in the urban forest, although supplemental feeding was present only in the other study area.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…A contrasting pattern was reported for body mass and body condition of Eurasian red squirrels in two urban areas: a park located in the city centre of Warsaw and an area described as an urban forest (Beliniak et al. 2022). Squirrels were heavier with better body conditions in the urban forest, although supplemental feeding was present only in the other study area.…”
Section: Resultsmentioning
confidence: 96%
“…Authors suggested that lower mass in the park could be due to the reduced necessity for individuals to accumulate fat where they have year‐round access to food or, since in urban park population density was greater, to increased intraspecific competition (Beliniak et al. 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations